THE IMPACT OF ENVIRONMENTAL PROJECTS ON ACHIEVING SUSTAINABLE DEVELOPMENT GOALS BY URBAN TERRITORIAL COMMUNITIES - DIACHUK, ANDRII; YEFREMOVA, OLHA; MATEYUK, OLESYA; SHEVCHENKO, SERGII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the modern scientific and practical environment of community management, balanced development is considered as a fundamental model of social progress and one of the main principles of effective local self-government. Strengthening and establishing the position of Ukraine as a democratic state requires the integration of the principles of sustainable development. At the same time, the process of decentralization of power in Ukraine actualizes the problematic aspects of ensuring the sustainable development of territorial communities.Achieving sustainable development goals is one of the main tasks for modern urban territorial communities, which face numerous environmental challenges such as pollution, increased anthropogenic pressure, biodiversity loss, urbanization, and climate change. The implementation of environmental projects becomes an important tool for ensuring the sustainable development of urban communities. These projects aim to improve the environmental condition of areas, reduce anthropogenic impact on the environment, and enhance the quality of life for the population.The article analyzes the impact of environmental projects on achieving sustainable development goals by urban territorial communities. It examines environmental projects that include infrastructure modernization, the implementation of alternative energy sources, the creation of green zones, the expansion of protected areas, and the improvement of waste management systems.The article considers the experience of implementing environmental projects in the Khmelnytskyi urban territorial community, including projects on waste management, the creation of green zones, and the improvement of water resources and air quality. Studies confirm that environmental projects contribute to economic growth by creating new jobs and promoting the development of entrepreneurship.The application of a comprehensive approach, sustainable development principles, and management technologies enables the effective implementation of environmental projects, promoting the balanced development of urban territorial communities.
Keywords: environmental project; sustainable development; community; ecology; natural resources